AdaBoost integration with Genetic Algorithm for Psychological Aptitude Result Interpretation Model - Bayu Hanif Pratama; Dadang Syarif Sihabudin Sahid (International ABEC, 2021)
SMA Darma Yudha Pekanbaru has a special program to facilitate students in knowing their interests and talents. The process is carried out by conducting special tests that can only be carried out by a certified psychologist. The psychologist is an educational worker under the division of guidance and counseling. The results of the test will be interpreted by psychologists with an output in the form of interests that can be used to determine the selection of majors in further study in college. Moreover, the results of the interpretation also contain recommendations of interest and talent for a career after the learner graduated from college. However, the recommendations of interest and talent are the result of unilateral analysis by psychologists without a supporting device to confirm the truth and accuracy. In this case the author will conduct research in the form of analysis of the results of interpretation issued by the psychologist of course with a variety of assessment instruments and not only that, to further ensure the results of interpretation, the author conducts analysis using 2 (two) machine learning methods and will then be done in order to get the best results. In this study, the authors used machine learning by comparing the results of analysis from 2 (two) methods namely Naïve Bayes and Decision Trees Classifier which then the classification results will be improved with AdaBoost.